Meanings of Community across Medieval Eurasia Comparative Approaches - Hovden, Eirik; Lutter, Christina; Pohl, Walter (Brill's Series on the Early Middle Ages, 2016)
How did Christianity, Islam and Buddhism frame the emergence and significance of particular communities in medieval Eurasia? This volume of well-linked comparative studies addresses the terminology of community, genealogies, urban communities and monasteries in medieval Europe, South Arabia and Tibet. Readership: Scholars, students and anyone interested in Medieval, Global, Cultural and Comparative History, Asian Studies, Historical Anthropology and Sociology and Religious Studies and academic libraries in these fields.